2013
DOI: 10.1121/1.4816543
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-term training on sound localization performance with spectrally warped and band-limited head-related transfer functions

Abstract: Sound localization in the sagittal planes, including the ability to distinguish front from back, relies on spectral features caused by the filtering effects of the head, pinna, and torso. It is assumed that important spatial cues are encoded in the frequency range between 4 and 16 kHz. In this study, in a double-blind design and using audio-visual training covering the full 3-D space, normal-hearing listeners were trained 2 h per day over three weeks to localize sounds which were either band limited up to 8.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(88 citation statements)
references
References 43 publications
7
74
0
Order By: Relevance
“…Contrary to the present work, neither of those studies observed improvements in polar angle errors, but this is probably more of a reflection of the differences in sensitivity of the localization performance measures in those studies compared to the current study. In a related and very recent study, Majdak et al (2013) used a similar training paradigm to help subjects accommodate to virtual auditory space stimuli that were either low passed at 8 kHz or where the DTFs were spectrally warped to shift the high frequency spectral information (2.8-16 kHz) into a narrower, low frequency region (2.8-8 kHz). Using measures similar to those used here, they showed training effects on both the PAE and %FB comparable to those reported here, although their training consisted of 21 days of two hour training sessions using a virtual display of visual and auditory stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the present work, neither of those studies observed improvements in polar angle errors, but this is probably more of a reflection of the differences in sensitivity of the localization performance measures in those studies compared to the current study. In a related and very recent study, Majdak et al (2013) used a similar training paradigm to help subjects accommodate to virtual auditory space stimuli that were either low passed at 8 kHz or where the DTFs were spectrally warped to shift the high frequency spectral information (2.8-16 kHz) into a narrower, low frequency region (2.8-8 kHz). Using measures similar to those used here, they showed training effects on both the PAE and %FB comparable to those reported here, although their training consisted of 21 days of two hour training sessions using a virtual display of visual and auditory stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has demonstrated that listeners are able to recalibrate to new HRTFs following a relatively prolonged period of exposure Carlile et al, 2007;Carlile and Blackman, 2014;Majdak et al, 2013). Presumably the quality of that spatial information will be dependent on both the extent of the locationdependent changes and the uniqueness of the spectral profiles for each location.…”
Section: Blur Polar Anglementioning
confidence: 92%
“…Further information about the CTC-filter were presented by Majdak et al [42]. The used HRTFs were those of the artificial head described in reproduction method III.…”
Section: Reproduction Methods Iii: Non-individual Binaural Stimuli Viamentioning
confidence: 99%